2023
DOI: 10.3390/molecules28186702
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanism of Chuanxiong Rhizoma against Thrombosis Based on Network Pharmacology, Molecular Docking and Experimental Verification

Shasha He,
Xuhua He,
Shujuan Pan
et al.

Abstract: Chuanxiong rhizoma (CX) has been utilized for centuries as a traditional herb to treat blood stasis syndromes. However, the pharmacological mechanisms are still not completely revealed. This research was aimed at exploring the molecular mechanisms of CX treatment for thrombosis. Network pharmacology was used to predict the potential anti-thrombosis mechanism after correlating the targets of active components with targets of thrombosis. Furthermore, we verified the mechanism of using CX to treat thrombosis via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Interaction analysis revealed that tangeretin molecules interact primarily within the hydrophobic pocket of CutC protein. The docking simulations ( Figure 6 E) indicated a docking energy of −32.6549 kJ/mol for the tangeretin and CutC protein complex, exceeding the threshold of −29.301 kJ/mol [ 21 ]. This result suggests a strong binding relationship between tangeretin and CutC protein.…”
Section: Resultsmentioning
confidence: 99%
“…Interaction analysis revealed that tangeretin molecules interact primarily within the hydrophobic pocket of CutC protein. The docking simulations ( Figure 6 E) indicated a docking energy of −32.6549 kJ/mol for the tangeretin and CutC protein complex, exceeding the threshold of −29.301 kJ/mol [ 21 ]. This result suggests a strong binding relationship between tangeretin and CutC protein.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking is now widely used in the research of active ingredients in TCM and herbal formulas based on specific targets. [23][24][25] Therefore, we have developed a comprehensive approach to explore the active chemical compounds of ZBDHP and their potential mechanisms in the treatment of CPP based on UHPLC-Q-Exactive Orbitrap-MS analysis, network pharmacology analysis, and molecular docking. In this study, chemical compounds of ZBDHP were rapidly identified using the UHPLC-Q-Exactive Orbitrap-MS method, and their mechanisms were predicted using network analysis, with results verified using molecular docking.…”
Section: Introductionmentioning
confidence: 99%